On Political Communication: Is Social Media More Effective? - Fitriyasa Meiserli (Resolusi: Jurnal Sosial Politik, 2021)
The effectiveness of political communication is a necessary result to build a synergistic political system. Many media are used for political communication. Recently, mass media like printed and electronic media are not only the communication platforms. There is also social media considered very influential on the political communication. The model of political communication that occurs in the digital era is now very different from the last few years. Media or forums for political communication are already very diverse. In this era, all political communication media can be done on social media platforms. With social media, many barriers can be minimized. It cuts the costs and is more practical to build communication between public officials and their constituents. Yet, the absent of physical presence in social media could undermine how effective is indirect-communication without having a face-to-face or physical meeting. Does social media provide more effective features in the way of political communication? This study discusses several essential things in building and measuring the effectiveness of political communication between public officials and the community regarding the current development of communication.